Can Nutrition or Inflammation Moderate the Age-Cognition Association Among Older Adults? - Handing, Elizabeth P; Small, Brent J; Andel, Ross; McEvoy, Cathy L; Kumar, Nagi (The journals of gerontology. Series B, Psychological sciences and social sciences, 2019)
OBJECTIVES: Previous research has shown that nutrition can influence cognitive abilities in older adults. We examined whether nutritional factors or inflammatory biomarkers moderate the age-cognition association. METHOD: Analyses included 1,308 participants (age ≥60) from the National Health and Nutrition Examination Survey III. Macronutrients (% of calories from fat, protein, and carbohydrates), micronutrients/amino acids (blood serum values: Vitamins B12, C, D, E, folate, iron, homocysteine, and β-carotene), and inflammatory biomarkers (serum C-reactive protein, plasma fibrinogen, and serum ferritin) were examined as moderators with cognition. Cognition was measured by six tasks: immediate and delayed story recall, immediate and delayed word memory, digit subtraction, and questions about place/orientation. RESULTS: Higher values of serum folate were significantly associated with better cognitive scores. Specifically, the interaction between age-cognition and folate indicated the associations of higher age and lower global cognition and lower immediate story recall were weaker in those with higher folate values (p's < .05). A significant interaction between age and plasma fibrinogen indicated that the association between age and worse digit subtraction was stronger with values >3.1 g/L. DISCUSSION: Folate and fibrinogen were significant moderators between age and cognition. Further research into the relationship between nutrition, inflammation, and cognitive aging is needed.
Keywords: nutriční stav; zánět; výživa - přehledy; Cognition; Age Factors; Ferritins; Humans; biologické markery; Aged; Fibrinogen; železo; kognitivní dysfunkce; senioři; Male; Nutritional Status; Biomarkers; beta Carotene; lidé středního věku; Homocysteine; lidé; beta-karoten; mužské pohlaví; Female; Folic Acid; Vitamins; věkové faktory; kyselina listová; neuropsychologické testy; C-Reactive Protein; Middle Aged; Cognitive Dysfunction; Iron; Neuropsychological Tests; Diet; ferritin; homocystein; ženské pohlaví; Inflammation; C-reaktivní protein; Nutrition Surveys; dieta; vitaminy; kognice; fibrinogen